Soil fertility improvement in agroforestry after 30 years of silvopasture on ferric lixisols within the Guinea Savanna ecology of Nigeria - Mesele, S.A.; Adelana, F.O.; Mechri, M. (Elsevier, 2025)
This research examines the sustained enhancement of soil fertility in the Guinea Savanna of Nigeria, by comparing silvopasture and cropland systems on ferric lixisols, soils known for low fertility and nutrient retention. The research addresses the pressing issue of soil degradation in Fasola area of Oyo State, Nigeria.A silvopastural system established over three decades was assessed and compared with conventional arable land using a fixed grid sampling technique across 30 sampling locations for each land-use system within a 1000 ha. The assessment focused on the topsoil layer of 0–20 cm depth. The soil samples were analyzed for pH, organic carbon content, total nitrogen, available phosphorus, and other exchangeable cations and the soil micronutrients, using wet chemistry standard procedures. The results showed that the silvopastural system considerably enhanced soil fertility. Organic carbon increased by 290 %, total nitrogen by 183 %, and available phosphorus by 150 % compared to cropland soils. Additionally, concentrations of exchangeable cations, such as calcium (325 % increase), magnesium (400 % increase), and potassium (300 % increase), were substantially higher in silvopasture systems. Micronutrient levels, including zinc, copper, iron, and manganese, also significantly increased. The results show that silvopastural system provides a feasible technique for long-term soil fertility increases, delivering essential advantages for sustainable agriculture and soil management in the Guinea Savanna ecology. Silvopastoral system, through nitrogen cycling and water retention, may aid in the rejuvenation of degraded soils and improve crop productivity in nutrient-depleted soils.